The Bans and the Boons of Large Number of Students on the Process of Teaching English as a Foreign Language - BENZEKHROUFA, Hanane (My University, 2017)
Teaching and learning English as a foreign language has always been an area of ​​investigation, as it has dealt with many issues and conflicts about how it takes in law. To achieve an effective teaching and learning process, we must consider the three main elements: the teacher, the students, and the physical environment that constitutes the classroom where this process takes place. This is the class where both teachers must teach successfully and students feel comfortable and comfortable learning the best.
The Case of First and Third Year LMD Students at University of Mostaganem
Keywords: Learning english as a foreign language; Teachers; Learners; Environment